2019
DOI: 10.3201/eid2503.180686
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Calmette-Guérin Cases Reported to the National Tuberculosis Surveillance System, United States, 2004–2015

Abstract: TOC summary: Clinical history can discern probable BCG cases from TB cases, enabling optimal clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Adverse events following immunization with BCG are considered underreported since assays to confirm isolates as BCG are still relatively rare. Moreover, based on the routine laboratory diagnostics and even molecular techniques, it is difficult to associate the clinical BCG isolates with the particular vaccine lot administered [15][16][17][18][19][20]. Therefore, the contribution of BCG genomic heterogeneity to the viability and residual virulence of vaccine populations in vivo remains unclear in terms of the development of BCG-related disease that otherwise can be associated with immune responses and human genetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse events following immunization with BCG are considered underreported since assays to confirm isolates as BCG are still relatively rare. Moreover, based on the routine laboratory diagnostics and even molecular techniques, it is difficult to associate the clinical BCG isolates with the particular vaccine lot administered [15][16][17][18][19][20]. Therefore, the contribution of BCG genomic heterogeneity to the viability and residual virulence of vaccine populations in vivo remains unclear in terms of the development of BCG-related disease that otherwise can be associated with immune responses and human genetics.…”
Section: Discussionmentioning
confidence: 99%
“…The attenuated BCG vaccines are believed safe and effective mainly to prevent the most severe meningitis and miliary forms of childhood TB associated with high mortality in infants and young children, especially in high TB-burden countries [1,2]. However, adverse events following immunization with BCG in 1-10% of vaccinees are likely to be substantially underreported since assays to confirm isolates as BCG are still relatively rare [15][16][17][18][19][20] despite the advent of molecular techniques and commercially available kits for BCG identification [21]. In Russia, the estimated frequency of complications per 100,000 BCGimmunized decreased from 35.3 in 2005 to 11.2 in 2013 [22].…”
Section: Introductionmentioning
confidence: 99%
“…This study also reported mycotic aneurysms in 5.7% of systemic BCG cases and found that those with vascular involvement had a mortality rate roughly four times baseline (16.7% vs 4.5%). A study looking at 118 BCG cases reported to the US National Tuberculosis Surveillance System from 2004 to 2015 reported that genitourinary and skeletal systems were most commonly affected, with only 3% of cases having pleural, and none meningeal involvement (Wansaula et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of Pott's disease or disseminated BCG in general can be challenging. Extrapulmonary findings of disseminated BCG are difficult to detect with sputum smears, with only 4 of 118 total cases reported to the CDC from 2004 to 2015 testing positive [ 10 ]. Emphasis must be placed on sampling multiple locations suspected of disease and using genetic assay such as spacer oligonucleotide, mycobacterial interspersed repeating units, and variable number of tandem repeats [ 4 ].…”
Section: Discussionmentioning
confidence: 99%